Advances in Characterizing and Addressing Land Degradation and Associated Ecosystem Responses - Zhan, Jinyan; Zheng, Xinqi; Hasan, Shaikh Shamim; Cheng, Wei (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Land degradation, exacerbated by climate change and rapid urbanization, poses significant threats to socio-economic development. There is an urgent need to explore land degradation and its associated ecosystem responses and the suitable pathways for sustainable development in urban and rural regions. This reprint comprises a collection of 16 articles, featuring 1 review article and 15 research articles. There are some key practical experiences and scientific findings to support the ecosystem change response to land degradation, through either theoretical works or empirical research, identifying the characteristics and solutions for sustainable development. Key scientific issues addressed include land use and land cover change, ecological impacts of urbanization, mechanisms of land degradation on ecosystems, and coordinated social, economic, and ecological development. This reprint encouraged scholars to share the latest advancements in the research framework, datasets, methods, and case studies for assessing land degradation and associated ecosystem responses. We expect this reprint will inspire broader reflection and discussion within academic community regarding the theories and practices concerning land degradation and associated ecosystem responses. It could be a valuable reference for exploring potential solutions towards achieving land degradation neutrality and promoting regional sustainable development.